Antimicrobial and synergistic effect of Moroccan native Argania spinosa essential oil for modulating of antibiotics resistance. Issue 24 (17th December 2021) - Nafis, Ahmed; Hassani, Lahcen; Marraiki, Najat; Al-Rashed, Sarah; Elgorban, Abdallah M.; Syed, Asad; Iriti, Marcello
Abstract: In this study, the chemical composition and antimicrobial activity of the essential oil (EO) extracted from leaves of the Moroccan endemic plant Argania spinosa were investigated for the first time, to the best of our knowledge. In addition, the EO antimicrobial activity was evaluated in combination with two known antibiotics (ciprofloxacin and fluconazole), in order to ascertain possible synergistic effects. The chemical composition analyzed by GC/MS showed that A. spinosa EO was characterised by the abundance of geranyl acetate (19.18%), methyleugenol (10.98%), linalyl acetate (10.59%) and eucalyptol (8.49%), and monoterpene hydrocarbons was the major class. EO showed an antimicrobial potential against all tested microorganisms. The highest activity was recorded against Gram positive bacteria and yeasts with MICs ranging from 7.75 to 15.5 mg/mL and from 3.88 to 7.75 mg/mL, respectively. The Gram negative bacteria were the most resistant with MICs of 31 mg/mL. The mixture of EO at sub-inhibitory concentrations with conventional drugs exhibited a significant decrease in their individual MICs from 4 to 32 fold. The highest level of synergy was observed for ciprofloxacin against Staphylococcus aureus, Bacillus subtilis and Escherichia coli . Despite the antimicrobial activity of A. spinosa EO is weak, the results of the current study suggest a potential synergy between EO and antibiotics in the goal to modulate drug resistance. Graphical Abstract: UF0001